How can critical thinking be recognised and developed in students that are still developing tertiary-level English language proficiency? - Clark, Lorna (Advancing Scholarship and Research in Higher Education, 2022)
As many international students attending Western universities do not have English as their first language, they can experience difficulty sharing their wealth of ideas. As critical thinking and academic writing are often mutually dependent, this study sought to explore how international students express their ideas and how this can be further supported in the classroom. Using educational design research, 20 tertiary foundation students received 12 weeks instruction in critical thinking and academic writing and their output assessed pre and post course. The study established that students could demonstrate critical thinking on entry to the program and, with focused instruction, were able to further enhance their skills. However, findings also illustrate that the students did not possess the same ability to construct advanced written representation of their ideas. This study suggests that consideration be given to alternate methods of assessment and instruction that recognise international students’ existing critical thinking skills base.